Subclonal TP53 and KRAS variants combined with poor treatment response identify ultrahigh-risk pediatric patients with T-ALL - Kempter, Tamara; Richter-Pechańska, Paulina; Michel, Katarzyna; Rausch, Tobias; Erarslan-Uysal, Büşra; Eckert, Cornelia; Zimmermann, Martin; Stanulla, Martin; Schrappe, Martin; Cario, Gunnar; Köhrer, Stefan; Attarbaschi, Andishe; et al. (Blood advances, 2025)
Variations in the TP53 and KRAS genes indicate a particularly adverse prognosis in relapsed pediatric T-cell acute lymphoblastic leukemia (T-ALL). We hypothesized that these variations might be subclonally present at disease onset and contribute to relapse risk. To test this, we examined 2 cohorts of children diagnosed with T-ALL: cohort 1 with 81 patients who relapsed and 79 who matched nonrelapsing controls, and cohort 2 with 226 consecutive patients, 30 of whom relapsed. In cohort 1, targeted sequencing revealed TP53 clonal and subclonal variants in 6 of 81 relapsing patients but none in the nonrelapsing group (P = .014). KRAS alterations were found in 9 of 81 relapsing patients compared with 2 of 79 nonrelapsing patients (P = .032). Survival analysis showed that none of the relapsed patients with TP53 and/or KRAS alterations survived, whereas 19 of 67 relapsed patients without such variants did, with a minimum follow-up time of 3 years (P = .023). In cohort 2, none of the relapsing patients but 10 of 196 nonrelapsing patients carried TP53 or KRAS variants, indicating that mutation status alone does not predict poor prognosis. All 10 nonrelapsing patients with mutations had a favorable early treatment response. Among the total cohort of 386 patients, 188 showed poor treatment response, of whom 69 relapsed. Of these poor responders, 9 harbored TP53 or KRAS variants. In conclusion, subclonal TP53 and KRAS alterations identified at the time of initial diagnosis, along with a poor treatment response, characterize a subset of children with T-ALL who face a dismal prognosis and who may benefit from alternative treatment approaches.